DEVELOPMENT OF MOODLE-BASED E-MODULES ON MOTION SYSTEMS FOR ELEVENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL - Reza Hendrawan; Zulfarina Zulfarina; Irda Sayuti (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2022)
This study aims to develop e-module teaching materials with the Moodle application on motion system materials. This e-module with the Moodle application has several advantages, namely learning is more interesting and can be done remotely where educators can still control learning and assessment activities, there are discussion forums and quizzes and has security features limiting access rights where unregistered users cannot open e- module. This research is a type of research and development (R&D). The procedure for developing this research uses the ADDIE development model, where this development model consists of 5 stages, namely Analysis (analysis), Design (design), Development (development), Implementation (implementation) and Evaluation (evaluation). The research instrument was a validation sheet and a respondent's questionnaire. The media validation stage involved 5 subjects (1 media expert, 1 material expert, 1 linguist, 1 pedagogic expert, and 1 teacher). Feasibility assessment by experts using validation sheets. The practical test phase involved 5 people, the simulation test involved 5 master students at the University of Riau majoring in biology and teachers and the limited trial involved 40 students. The data analysis technique is to calculate the percentage of validation assessment scores and user responses. The results showed that the Moodle- based e-module developed met the very valid criteria with an average of 3.54, the practical aspect showed very practical with an average of 94.54, and the results of the student response test obtained a score of 96.4 with a very good category good. Based on the description above, it is concluded that the Moodle-based e- module that was developed can be a source of learning/teaching materials that can be used during learning because with the Moodle-based e-module the material presented is more interesting, educators can include videos, animations, pictures and learning can also be done remotely where educators can still control and evaluate students.